Clinical Analysis of Renal Failure Caused by Malakoplakia: A Case Report and Literature Review - Wang, Zhenting; Ren, Jiannan (Frontiers in Medicine, 2022)
Background: A 52-year-old middle-aged woman developed fatigue, poor appetite and elevated CRE levels six months ago without known causes of these symptoms. After repeated anti-infective and renal function improvement treatment, her symptoms did not significantly improve and local progress. Pathological examination confirmed soft spot disease of left kidney and bladder. Tests: Plain computed tomography (CT) scan of the lungs and urinary system; CT enhancement of the abdomen and pelvis, magnetic resonance (MR) enhancement of the abdomen and pelvis; positron emission tomography (PET)-CT; ultrasonography of the urinary system; cystoscopy, biopsy; and laboratory examination including urine routine and culture, urine protein quantification, cytology and culture of drainage fluid smear, routine blood test, and assessment of C-reactive protein, sedimentation, procalcitonin, liver function, renal function, electrolytes, thyroid function, parathyroid function, and cardiac enzymes. Diagnosis: Left-sided renal and bladder malakoplakia, chronic renal insufficiency (CKD stage 4), renal anemia, complicated urinary tract infection (Escherichia coli + smooth bacilli), chronic urinary retention, abscess of the left psoas major and iliac fossa, type II diabetes mellitus, grade III hypertension (very high risk), and post cholecystectomy. Treatment: Hospitalized urinary catheterization, anti-infective treatment, diagnostic anti-tuberculosis treatment, gastrointestinal dialysis, correction of anemia treatment, nutritional support, left lumbar enlargement, iliac fossa abscess puncture drainage, left nephrectomy.